Performance Evaluation of Solar Panel with Reflector Using Nano Fluids - Ibrahim, A. T.; Abdullahi, A. A.; Mustapha, A. T.; Nura, J.; Bala, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This research evaluated the performance of solar panel with reflector using Nano Fluids in Kano State, Nigeria. An experimental setup was designed, consisting of a solar panel without modification PWM, solar panel with reflectors PWR, solar panel with reflectors and a water-cooling system (PWRC). The experiments were conducted at the optimum tilt angle of 12o in Kano State. Additionally, models were developed using SolidWorks of PWR and PWRC to simulate the thermal behavior of the panel with different coolant types, including water, ethylene glycol, and urea liquid using ANSYS. The results indicate that ethylene glycol exhibited the lowest rate of increase in the panel’s surface temperature (ST), followed by urea liquid and then water. For an initial surface temperature (ST) of 27.5°C, 64.2°C, and 46.1°C, the panel using ethylene glycol experienced temperature increases of 22.072°C, 74.184°C, and 33.951°C, respectively, over a duration of 50 minutes. In the case of water, the panel’s ST rose by 33.155°C, 80.388°C, and 59.698°C under the same initial ST conditions. Similarly, the panel using urea liquid witnessed surface temperature increases of 24.648°C, 74.282°C, and 35.498°C for the respective initial ST values of 27.5°C, 64.2°C, and 46.1°C